The experience of stress among new clinical nurses - Mahbobeh Sajadi Hezaveh; Forough Rafii; Sharareh khosravi; Naiemeh Seyedfatemi (Tehran University of Medical Sciences, 2015)
Background & Aim: Stress is a common phenomenon in nursing profession, but novice nurses usually experience more stress. This stress can result in job dissatisfaction and quitting the occupation. This study aimed to explore the novice nurses' experience of stress at the beginning of their clinical practice. Methods & Materials: This study was conducted using a qualitative content analysis. The study population consisted of 17 novice nurses working in hospitals affiliated to Tehran University of Medical Sciences in Iran, selected through purposive sampling. Data were collected through semi-structured interviews. Results: Four themes and 7 categories emerged during data analysis. The extracted themes and categories consisted of (I) insufficient competency (inadequate knowledge, inadequate practical skills, inappropriate communication skills), (II) clinical workplace (workplace environment, workplace climate), (III) clients' challenges (patient's physical and psychological status, family and relatives' behavior), and (IV) colleagues' behaviors. Conclusion: Novice nurses expressed that they had high levels of stress in their first months of employment. The study showed various factors causing stress among participants which may result in quitting their work. Considering novice nurses' experience of stress, and underlying factors, nursing managers can help to reduce novice nurses' stress and increase their motivation to continue their work.